Anthroponyms of the Polish-Czechborder area (The Moravian Gate) - Mieczysław, BALOWSKI (Bohemistyka, 2020)
The author describes in the article project of researching the anthroponymy of the Polish-Czech borderland on the section of the Moravian Gate (Gorzyce – Krzyżanowice municipalities on the Polish side and Hať – Hilheřovice – Bohumín municipalities on the Czech side). The described borderland belongs to the so-called transitional borders, whose characteristic feature is the mixing of the population of two or more nations (or ethnic groups), and the effect of it is movement of the population in this area. As a result, the so-called third culture has developed, which had a major impact on the shape of names of the inhabitants, as well as on the choices of names for their children. Another factor in changing the form of surnames is the interference of an official who has often changed the spelling form of the surname in accordance with the language norm in force in his native language.